Modeling and Optimization of Transition Metal-Catalyzed Peracetic Acid Oxidation for Advanced Polishing of Biologically Treated Leachate - Unal, Emre; Tuncak, Ceyda; Yilmaz, Rabia Nefise; Can-Guven, Emine; Yazici Guvenc, Senem; Varank, Gamze (AMER CHEMICAL SOC, 2026)
The treatment of landfill leachate is a significant environmental challenge because of its high concentration of resistant organic pollutants that are difficult to remove using conventional methods. This study aimed to remove resistant organic matter from the membrane bioreactor effluent (MBR) of leachate through the use of advanced oxidation processes. The catalytic effect of transition metals (Fe2+, Zn2+, Cu2+, Mn2+, Ni2+, and Co2+) was evaluated, where peracetic acid (PAA) was used as the oxidant. Among the applied processes, the highest pollutant removal was obtained by Fe2+/PAA, Co2+/PAA, and Mn2+/PAA processes. The Box-Behnken design was used for parameter optimization of these processes. The initial pH, catalyst dose, and oxidant dose were independent variables, whereas COD and UV254 removal efficiencies were system responses. Regression models describing COD and UV254 removal through Fe2+/PAA, Co2+/PAA, and Mn2+/PAA processes were developed, and the data obtained were analyzed by analysis of variance. Under the optimum conditions for the Fe2+/PAA process (pH: 3.13, Fe2+: 0.233 mM, PAA: 2.25 mM), the COD and UV254 removal were 86.1% and 87.5%, respectively. For the Co2+/PAA process under optimum conditions (pH: 3.93, Co2+: 0.298 mM, PAA: 2.16 mM), the COD and UV254 removal were 80.2% and 86.0%, respectively. For the Mn2+/PAA process under optimum conditions (pH: 3.12, Mn2+: 0.299 mM, and PAA: 2.22 mM), the COD and UV254 removal were 84.0% and 84.8%, respectively. These results showed that the optimized transition-metal-catalyzed PAA processes provide a highly efficient approach for the advanced treatment of real leachate MBR effluent.
Keywords: WASTE-WATER; DEGRADATION; REMOVAL; Chemistry